Faktor yang Memengaruhi Tingkat Ketahanan Pangan Wilayah Di Kecamatan Sigi Biromaru - Jumariati Jumariati; Max Nur Alam; Lien Damayanti (Universitas Tadulako, 2019)
utilization on food security in Sub Sigi Biromaru and analyze the relationship between food availability, food access and food utilization in District Sigi Biromaru. The method used was descriptive method survey to determine the location of intentionally (purposive), type of data used secondary data sourced Time series of profiles 6 villages in the subdistrict representative Sigi Biromaru represent districts of Sigi Biromaru. The analysis showed that the independent variables (Xi) jointly significant effect on the dependent variable (Y) levels of food insecurity Biromaru Sigi district area, this is indicated by the value of the F-count 3246.506> F-table sig 19.16. 2 tile Adstj2 0.000 R2 = 0.999 means a 99.9% value variation of the food security area (Y) can be explained by variable food availability (X1), food access (X2), and utilization of food (X3), and the remaining 0.1% described other models. Value variations in the level of food security region (Y) can be explained by variable food availability (X1), Access to food (X2), and Utilization of Food (X3), regression coefficient / elasticity of food availability (X1) = 0.103, Access to food (X2) = 0.942, Utilization of Food (X3) = 0.606. The results of the analysis of the relationship of food availability, food access and food utilization level of food security to the region shows the influence of both direct and indirect effect on food security in the sub district of Sigi Biromaru.